REKONSTRUKSI KURIKULUM BERBASIS PEMIKIRAN IBNU KHALDUN: ADAB, AKAL, DAN INTERAKSI SOSIAL SEBAGAI RESPONS KRISIS KARAKTER DI ERA DIGITAL - Abdul Aziz, Faqih; Wahyu Wijaya, Adept; Robi' Rozaqiy, Rohmat; Tazkiyyah, Iffatut; Rachman Assegaf, Abd (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The sweeping tide of digital transformation has precipitated a significant character crisis, evidenced by phenomena such as cyberbullying, disinformation, erosion of empathy, and digital narcissism. Contemporary curricula often fail to address these challenges at a fundamental level, tending toward partial solutions that lack a robust philosophical foundation. This study seeks to bridge that gap by formulating a curriculum reconstruction model grounded in Ibn Khaldūn’s educational thought. Employing qualitative library research and a philosophical–conceptual analytic approach, the study examines three core pillars in Ibn Khaldūn’s framework: adab (ethical comportment), ʿaql (critical rationality), and social interaction (ʿasabiyyah/collective solidarity). The findings indicate that these pillars are highly pertinent to the digital context: adab provides a basis for digital ethics; ʿaql undergirds critical information literacy; and social interaction fosters positive digital communities. Building on this analysis, the study proposes an integrative curriculum reconstruction model encompassing principles, aims, content recommendations, instructional strategies, and a holistic evaluation system. The model contributes both theoretically and practically by offering a rigorous framework to cultivate a generation that is not only digitally proficient but also morally grounded, integrous, and socially responsible amid the complexities of digital civilization.